Study of the Android and ANN-based Upper-arm Mouse - Hartawan Sugihono; Romy Budhi Widodo; Oesman Kelana (IAES Indonesia Section, 2018)
Disability is a person's condition in the physical, intellectual, mental, and/or sensory limitations in the long term. This study is reserved for those who do not have the lower arm in order to operate the computer normally. This study uses orientation sensor on the smartphone as the main sensor to move the cursor and click. Delivery of data from smartphone to computer is using Bluetooth. This study will compare two gestures from a combination of orientation sensors on the upper arm: gesture 1 using pitch-yaw motion and gesture 2 using pitch-roll motion; to move the cursor on the monitor. Left-click and right-click using ANN is to detect upper arm jerk movements. Evaluation using ISO/TS 9241-411 standard: ergonomics of human-system interaction; which includes performance evaluation and comfort of the gesture. Performance results of throughput, movement time, comfort and fatigue between gestures were not significantly different between those gestures. The result of the effort questionnaire is that gesture 1 has the highest effort on the shoulder and gesture 2 has the highest effort on the hand.